SOSIALISASI PEMANFAATAN MEDIA AUGMENTED REALITY PADA SISWA KELAS IV SD - Syafriza, Azizatul Alif; Nuryatno, Edy Tri; Ayuningtyas, Astika; Ferryka, Putri Zudhah (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
The purpose of this community service is to provide socialization to elementary school students, especially grade IV, in four locations related to Augmented Reality media. Learning today is not limited only to books or explanations from teachers. Learning today can utilize technological developments. Gadgets that have been a means of entertainment can be used as learning media. The use of gadgets as learning media can provide different facilities so that they can foster student learning motivation. It is hoped that after this socialization activity, students will have broader knowledge related to learning media. Developing technology can be a fun learning medium for students.